2021
DOI: 10.3390/ijerph18189647
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Cognitive Complaints and Depressive Symptoms with Health-Related Quality of Life and Perceived Overall Health in Japanese Adult Volunteers

Abstract: Cognitive complaints, defined as perceived cognitive dysfunction in daily living, are associated with depressive symptoms. The associations of cognitive complaints and depressive symptoms with health-related quality of life (HRQoL) and perceived overall health in Japanese adults remains unknown. To investigate these relationships, we evaluated a convenience sample of 525 Japanese adult volunteers (Mage: 41.3 ± 11.7; 238 male and 287 female). We used the Cognitive Complaints in Bipolar Disorder Rating Assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
1
2
1
Order By: Relevance
“…Low IC reserve has been verified to be associated with worse physical, mental, and total QoL (Ma et al, 2020). Some domains of IC, such as sensory (Harithasan et al, 2020;Zhang et al, 2021), locomotion (Henchoz et al, 2017), cognition (Bouldin et al, 2021), and depressive symptoms (Toyoshima et al, 2021), were shown to be related to HRQoL. The present study extends our knowledge about the different effects of IC domains on domain-specific HRQoL.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Low IC reserve has been verified to be associated with worse physical, mental, and total QoL (Ma et al, 2020). Some domains of IC, such as sensory (Harithasan et al, 2020;Zhang et al, 2021), locomotion (Henchoz et al, 2017), cognition (Bouldin et al, 2021), and depressive symptoms (Toyoshima et al, 2021), were shown to be related to HRQoL. The present study extends our knowledge about the different effects of IC domains on domain-specific HRQoL.…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, cognitive decline, a common neurological disease in elderly, characterized by biological damage in the limbic system of the brain, is considered an exemplification of how, from a neurobiological abnormality, one transitions to a psychological feeling (hopelessness, which is also one of the subcomponents of the definition of demoralization) and vice versa (Clarke and Kissane, 2002;Costanza et al, 2015). In fact, depression might be the intermediate mediator between cognitive impairment and mental health (Toyoshima et al, 2021). Unfortunately, the reported negative relationship between cognitive impairment with mental health in the psychological dimension of HRQoL (Bouldin et al, 2021) was not found in this study.…”
Section: )contrasting
confidence: 63%
See 1 more Smart Citation
“…HRQoL was measured by the EuroQol-5 dimension, which consists of a five-dimensional classification system. 25 , 26 EQ5D-5L has five dimensions: mobility, self-care, daily activities, pain/discomfort, and anxiety/depression. Each dimension has five levels: no difficulty, a little difficulty, moderate difficulty, serious difficulty, and very serious difficulty.…”
Section: Methodsmentioning
confidence: 99%